Reducing Unemployment Malaise in Nigeria: The Role of Electricity Consumption and Human Capital Development - Afolayan, Olufunmilayo T.; Okodua, Henry; Matthew, Oluwatoyin; Osabohien, Romanus (International Journal of Energy Economics and Policy, 2019)
One of the greatest challenges that Nigeria is confronted with and which on the average has continued to witness a rising trend over the years is unemployment. Its scourge is known to be responsible for a high level of poverty, inequality, increasing rate of criminality and general low level of living in the country. This study examined how electricity consumption and human capital can be used to reduce unemployment in Nigeria. The study obtained secondary data and analysed the data with the Johansen co-integration technique. The study found out that electricity consumption negatively impact unemployment, so also is government education expenditure. The result showed that a 1% increase in electric power consumption will lead to about 0.22% decline in the level of unemployment and 1% increase in education expenditure will bring about 0.17% decrease in the rate of unemployment. Therefore, the study recommends that the government should put in place policies and measures that will enhance the turn-out of quality graduates with skills and competence to chant the course of development by all stakeholders in the education sector. Keywords: Unemployment, Electricity Consumption, Government Education Expenditure. JEL Classifications: E24, L94, H52 DOI: https://doi.org/10.32479/ijeep.7590